(untitled) (Bulletin of criminological association of Ukraine, 2025)
It is argued that the first step should be to “simplify” administrative proceedings, which in turn will contribute to a faster and more effective consideration of cases. In this context, it is necessary to implement a set of measures, in particular: first, to ensure a reduction in the terms of consideration of administrative cases. This should include creating conditions for the introduction of information technologies, as well as expanding opportunities for pre-trial settlement of disputes; second, to review procedural norms that, in particular, regulate the procedure for considering minor cases. It is emphasized that the introduction of international standards in the context of the issues presented in the work is of paramount importance, since their full application in Ukrainian realities will allow: first, to strengthen guarantees for a fair trial, which includes equality of parties before the law, adversarial process, etc.; second, to strengthen the independence of the judicial system in general, and judges in particular, minimizing the risks of political or any other pressure; thirdly, it will increase the overall efficiency of the judicial system, since, for example, the establishment of strict deadlines for considering cases, electronic justice, simplification of certain procedural procedures, as it is seen, will allow avoiding the delay of legal proceedings and will improve access to justice. All of the above will lead to an overall increase in the level of trust in the judiciary, reduce the number of cases in international courts and make the national judicial system more predictable and effective.